2021
DOI: 10.3390/polym13121946
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microbial Products in Green Enhanced Oil Recovery: Acetone and Butanone

Abstract: Green enhanced oil recovery is an oil recovery process involving the injection of specific environmentally friendly fluids (liquid chemicals and gases) that effectively displace oil due to their ability to alter the properties of enhanced oil recovery. In the microbial enhanced oil recovery (MEOR) process, microbes produce products such as surfactants, polymers, ketones, alcohols, and gases. These products reduce interfacial tension and capillary force, increase viscosity and mobility, alter wettability, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Other processes [ 1 ] include microbial enhanced oil recovery (MEOR). MEOR [ 3 ] is an environmentally friendly enhanced oil recovery method that involves injecting microorganisms and produces surfactant, polymer, alcohol, ketone, acids, and gas in situ and enhances oil recovery. According to Haq [ 3 , 4 ], the green enhanced oil recovery (GEOR) is an eco-friendly EOR technique that involves the injection of specific green fluids, for example, surfactants, polymers, alcohols, acids, ketones, and gas (N 2 , CO 2 ) that effectively improves macroscopic and microscopic sweep efficiencies as a result increases residual oil recovery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other processes [ 1 ] include microbial enhanced oil recovery (MEOR). MEOR [ 3 ] is an environmentally friendly enhanced oil recovery method that involves injecting microorganisms and produces surfactant, polymer, alcohol, ketone, acids, and gas in situ and enhances oil recovery. According to Haq [ 3 , 4 ], the green enhanced oil recovery (GEOR) is an eco-friendly EOR technique that involves the injection of specific green fluids, for example, surfactants, polymers, alcohols, acids, ketones, and gas (N 2 , CO 2 ) that effectively improves macroscopic and microscopic sweep efficiencies as a result increases residual oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…MEOR [ 3 ] is an environmentally friendly enhanced oil recovery method that involves injecting microorganisms and produces surfactant, polymer, alcohol, ketone, acids, and gas in situ and enhances oil recovery. According to Haq [ 3 , 4 ], the green enhanced oil recovery (GEOR) is an eco-friendly EOR technique that involves the injection of specific green fluids, for example, surfactants, polymers, alcohols, acids, ketones, and gas (N 2 , CO 2 ) that effectively improves macroscopic and microscopic sweep efficiencies as a result increases residual oil recovery. Classification of GEOR, surfactant, and polymer flooding mechanisms and challenges in carbonates, a summary of literature review, knowledge gaps, the objective of the work, and an outline of the research are discussed in the following sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of microbes produces six chief metabolites (biosurfactants, biopolymers, biogas, biomass, bioacids, and biosolvents) that perform a dynamic role in the oil recovery process. These mechanisms include the reduction of oil viscosity, wettability modification, microbial plugging, reducing IFT, long hydrocarbon chain breakdown, and release of acids [14,17], as shown in Table 1. Azarhava et al [61] reported that when Bacillus licheniformis LMG 7559 was injected into the oil-saturated heterogeneous porous medium, it secreted extracellular Poly gamma-(glutamic acid), which enabled oil recovery of up to 31.45% using biopolymer flooding.…”
Section: Microbial Metabolic Products Involvedmentioning
confidence: 99%
“…However, for this purpose, highly advanced technologies will be quickly exhaust between a fraction of a quarter and half of a well's oil reserve. This high level of extraction is addressed with the aid of a tertiary technique, Enhanced Oil Recovery, or EOR (Figure 1) [17].…”
Section: Introductionmentioning
confidence: 99%